Synchronous neonatal telogen effluvium in white and black. - Chieco, P. (European Journal of Pediatric Dermatology, 2015)
During fetal life, the hair does not fall and does not grow randomly as in postfetal life, but it falls and grows in synchronous bands starting from the frontal region and moving towards the nape. In the latter site the last fall wave does not occur until the perinatal period. As a consequence of that often in the first few months of life you can observe a hair band of rarefaction with clear-cut borders in the occipital region. This phenomenon, which is called synchronous neonatal telogen effluvium (1) is therefore physiological. However, it is often interpreted as an effect of the pressure of the head on the pillow. This interpretation contrasts with the lack of a relationship between the place of rarefaction and the manner of sleeping of the newborn, which is often dictated by the case or fashions. In the black, due to the structure of the hair, the hair rarefaction area is much less well defined (2).